Deep Crustal Structure of the Eastern Central Asian Orogenic Belt Revealed by Integrated Magnetic-Gravity Imaging - Chang, Chang; Wang, Haiyan; Gao, Rui; Guo, Hua; Han, Song; Wu, Yangang (Frontiers in Earth Science, 2022)
The Central Asian Orogenic Belt (CAOB) is a globally magnificent accretionary orogenic belt that has been formed since the Phanerozoic as a result of the Paleozoic closing of the Paleo-Asian Ocean (PAO). The transition zone between the North China Craton (NCC) and the Siberia Plate is located in the eastern CAOB and has been thoroughly investigated by various seismic investigations. However, other types of geophysical approaches lag behind, especially integrated magnetic-gravity surveying, which could provide regional continent-scale constraints on the deep crustal structure. Here, the high-resolution ground gravity and airborne magnetic data covering the study region are newly processed by upward continuation, an improved potential field normalization differential algorithm, an analytical signal approach, and correlation analysis. The processed gravity and magnetic anomalies reveal dominant differences between the CAOB and the northern margin of the NCC; these regions are tectonically divided by the upper crustal Chifeng-Baiyan Obo fault, which is expressed by an important geological boundary. In the middle and lower crust, this tectonic boundary extends northward to the Xar Moron fault. Unexposed Mesozoic granites may be distributed extensively in the mid-lower crust along the Solonker suture zone. The local negative correlation characteristics of gravity and magnetic anomalies may be related to the structural fabrics derived from the convergence of the two terrains.